2017
DOI: 10.1016/j.jsat.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to and facilitators of pharmacotherapy for alcohol use disorder in VA residential treatment programs

Abstract: Among US military veterans, alcohol use disorder (AUD) is prevalent and in severe cases patients need intensive AUD treatment beyond outpatient care. The Department of Veterans Affairs (VA) delivers intensive, highly structured addiction and psychosocial treatment through residential programs. Despite the evidence supporting pharmacotherapy among the effective treatments for AUD, receipt of these medications (e.g., naltrexone, acamprosate) among patients in residential treatment programs varies widely. In orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 18 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…Pharmacological options include three FDA-approved medications (acamprosate, disulfiram, and oral or injectable naltrexone) (Jonas et al, 2014; NIAAA, 2007), and a fourth, topiramate, was found to have strong evidence for treatment of AUD in a meta-analysis (Jonas et al, 2014). Despite strong evidence for these treatments, they are underused among patients with AUD (Cohen et al, 2007; Harris et al, 2012; Rubinsky et al, 2015), and multiple barriers to treatment receipt and implementation have been documented (Alanis-Hirsch et al, 2016; Finlay et al, 2017; Hagedorn et al, 2016; Harris et al, 2013; Knudsen and Roman, 2014; Ober et al, 2017; Oliva et al, 2011; Williams et al, 2017a). People with infectious diseases (HCV and HIV) may be even less likely to receive evidence-based treatment for AUD compared to people without these conditions (Owens et al, 2018; Williams et al, 2017d).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological options include three FDA-approved medications (acamprosate, disulfiram, and oral or injectable naltrexone) (Jonas et al, 2014; NIAAA, 2007), and a fourth, topiramate, was found to have strong evidence for treatment of AUD in a meta-analysis (Jonas et al, 2014). Despite strong evidence for these treatments, they are underused among patients with AUD (Cohen et al, 2007; Harris et al, 2012; Rubinsky et al, 2015), and multiple barriers to treatment receipt and implementation have been documented (Alanis-Hirsch et al, 2016; Finlay et al, 2017; Hagedorn et al, 2016; Harris et al, 2013; Knudsen and Roman, 2014; Ober et al, 2017; Oliva et al, 2011; Williams et al, 2017a). People with infectious diseases (HCV and HIV) may be even less likely to receive evidence-based treatment for AUD compared to people without these conditions (Owens et al, 2018; Williams et al, 2017d).…”
Section: Introductionmentioning
confidence: 99%
“…The current study was part of a larger mixed-methods study to develop performance metrics specific to residential substance use disorder treatment programs based on electronic health record data (Ellerbe, et al, 2017; Finlay et al, 2017; Rubinsky et al, 2017). The study protocol was approved by the Stanford University Institutional Review Board (IRB) and the VA Palo Alto Research & Development committee.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the substantial individual, societal, and global public health burden of AUD, it appears to be largely untreated [1,15]. Even though effective pharmacotherapies for AUD have been available for decades and are supported by numerous systematic reviews and meta-analyses establishing both their efficacy and safety [16][17][18][19], drugs such as naltrexone and acamprosate have been found to be severely underutilized among AUD patients in select populations [20][21][22]. For example, in studies of US military veterans with AUD, fewer than 5% received any kind of pharmacotherapy [21,22].…”
Section: Introductionmentioning
confidence: 99%